Semi-circular angle-based one bit circle generation algorithm on a hexagonal grid. (2016) - Prabukumar, Manoharan; Ray, Bimal Kumar
In this paper, the idea of semi-circular angle-based circle generation algorithm on a hexagonal grid is proposed. It makes use of the advantages of hexagonal sampling that scan-convert the pixel on the raster with less scan-conversion error. The performance of the proposed algorithm is compared to that of the conventional circle generation algorithm on a hexagonal grid. The qualitative and quantitative analysis shows that the proposed algorithm outperforms the existing circle drawing algorithm on a hexagonal grid in terms of less computation cost.